2019
DOI: 10.1111/srt.12657
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐ and age‐related differences in facial sebaceous glands in Asian skin, as observed by non‐invasive analysis using three‐dimensional ultrasound microscopy

Abstract: Background While determining sebaceous gland morphology is useful in the treatment of skin disorders such as acne, a non‐invasive assessment method has not been developed. Since age and gender affect sebum level, differences in sebaceous gland morphology according to these factors were investigated. Methods Facial skin was measured using a high‐frequency three‐dimensional ultrasound microscope. First, the ultrasound images were compared with skin sections. Next, we assessed sebaceous gland morphology. Images o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…19 While concerning sebum production, males produced higher sebum levels than males. 20,21 Therefore, men should be at higher risk of developing more severe acne scar. However, the recent study did not find differences in skin type and the risk of more severe acne scar between gender.…”
Section: Discussionmentioning
confidence: 99%
“…19 While concerning sebum production, males produced higher sebum levels than males. 20,21 Therefore, men should be at higher risk of developing more severe acne scar. However, the recent study did not find differences in skin type and the risk of more severe acne scar between gender.…”
Section: Discussionmentioning
confidence: 99%
“…Gender: Sugawara et.al, 2019 reported cauliflowershaped sebaceous glands in male while young females had somewhat more cylindrical and smaller sebaceous glands than the young males [73]. There are significant morphological differences according to sex: total skin thickness is greater for men on most skin sites [56].…”
Section: E) Hormone and Metabolic Processesmentioning
confidence: 99%
“…Gender: Sugawara et al, 2019 reported cauli lower-shaped sebaceous glands in male while young females had somewhat more cylindrical and smaller sebaceous glands than the young males [76]. There are signi icant morphological differences according to sex: total skin thickness is greater for men on most skin sites [58].…”
Section: Other Intrinsic Issues Of Agingmentioning
confidence: 99%